The Notary's Responsibility For The Position of Fictitious Instrumental Witnesses in Authentic Deeds From The Perspective of The Notary Position Act - Amanda, Dina (Journal Research of Social Science, Economics, and Management, 2025)
An authentic deed is a written document made by a public official such as a notary, possessing perfect and binding evidentiary power under Indonesian law. This deed provides legal certainty through formal, material, and external proof in accordance with the provisions of the Notary Law (UUJN), including the presence of actual instrumental witnesses. However, the inclusion of fictitious instrumental witnesses can undermine the deed’s validity, reducing its evidentiary power to that of a private deed and potentially leading to its legal annulment. Such violations not only damage public trust and the professionalism of the notary but also expose the notary to administrative sanctions, civil liability, and criminal charges of forgery. Therefore, the integrity and professionalism of the notary are essential to maintaining the validity of authentic deeds, protecting legal rights, and ensuring legal certainty for all parties involved.